Multi-parameter in-process monitoring of clay dispersion during melt compounding with PLA - Teixeira, Paulo Francisco (2019)
The time evolution of organoclay particle size and volume fraction, as well as the shear viscosity, are measured in-line for a series of Poly(lactic acid)/organoclay composites, using a rheo-optical die coupled to a prototype modular co-rotating twin screw extruder. The small angle light scattering patterns and light attenuation recorded during transient experiments indicate that clay dispersion develops through melt intercalation between the clay galleries, thereby expanding the aggregates size, and eventually leads to aggregates break-up, i.e., exfoliation. The simultaneous recording of shear viscosity also indicates that smaller viscosities promote a faster melt intercalation and exfoliation but hinder the extent of clay dispersion. The methodology used in the present study validates the well accepted mechanism for clay dispersion and can be applied straight away for the monitoring of PNC manufacturing during practical production.